Open Key: Proceedings, Festschrifts, Gift Books And Compilations Published In The Fields Of Librarianship, Archiving And Documentation-Information - Mehmet Ali Akkaya (Türk Kütüphaneciliği)
One of the processes that is vital in terms of all disciplines at the point of scientific and qualified publishing is the literature search. A well planned and thorough literature search process will ensure that new studies to be put forward are holistic and original. This requires extensive, upto- date and well-organized secondary resources in the field concerned. The complete listing of information resources different than books and periodicals, such as proceedings, festschrifts, gift books and compilations and their contents, is very important not only in terms of the field concerned but also for our national knowledge production capacity and competence as well. It is precisely for this reason that “Open Key” of Polat and Odabaş, coming after a long and intense effort, is a reference source for the discipline of information science and its stakeholders in our country. “Open Key”, that indexes 2855 articles from 131 publications printed between 1960 and 2016, with its quantity and quality, strongly promises to be for many years one of the basic reference resources for information users.